2020
DOI: 10.1101/2020.03.30.015685
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recombination and purifying selection preserves covariant movements of mosaic SARS-CoV-2 protein S

Abstract: 22Following the recent report of a furin-like cleavage site unique to SARS-CoV-2, we characterized 23 additional amino acid residues, positioned within the crown of the spike (S) glycoprotein, under 24 diversifying selection along the ancestral lineage of currently circulating pandemic strains, and 25 affecting enhanced ability to infect host cells. Molecular dynamic simulations revealed long-26 range covariant movements of SARS-CoV-2 S glycoprotein monomer in pre-fusion conformation 27 with furin cleavage, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 123 publications
0
10
0
Order By: Relevance
“…This finding suggested that Bat-CoV-RaTG13 is the major recombinant parent of SARS-CoV-2 lineage. Based on these trees, and the signature pattern analysis ( Supplementary Table S3, Supplementary Figure S1 ) that showed that SARS-CoV-2 residues in these fragments are similar to the ones in Bat-CoV-RaTG13, we conclude that these genetic fragments are compatible with the whole genome phylogeny [ 38 ], and likely part of the main SARS-CoV-2 genetic backbone, inherited from a Bat-CoV-RaTG13 ancestor ( Figure 1 c). Yet, we cannot exclude that this genetic information was acquired by recombination with another ancestral/unsampled strain circulating in bats, other than Bat-CoV-RaTG13.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…This finding suggested that Bat-CoV-RaTG13 is the major recombinant parent of SARS-CoV-2 lineage. Based on these trees, and the signature pattern analysis ( Supplementary Table S3, Supplementary Figure S1 ) that showed that SARS-CoV-2 residues in these fragments are similar to the ones in Bat-CoV-RaTG13, we conclude that these genetic fragments are compatible with the whole genome phylogeny [ 38 ], and likely part of the main SARS-CoV-2 genetic backbone, inherited from a Bat-CoV-RaTG13 ancestor ( Figure 1 c). Yet, we cannot exclude that this genetic information was acquired by recombination with another ancestral/unsampled strain circulating in bats, other than Bat-CoV-RaTG13.…”
Section: Resultsmentioning
confidence: 72%
“…The topology of the phylogenies resulting from each recombinant fragment ( Figure 1 c) revealed the evolutionary history of each genetic fragment ( Figure 1 b,c). In detail, the phylogenetic tree based on the fragment 1 and 3 showed that SARS-CoV-2 is closely related to Bat-CoV-RaTG13, isolated from the bat species Rhinolophus affinis in Yunnan province in China in 2013 [ 38 ]. This finding suggested that Bat-CoV-RaTG13 is the major recombinant parent of SARS-CoV-2 lineage.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, variation in the region is comparable to numerous other conserved regions of the spike and to the viral genome as a whole. While Wong et al (19) and others (21)(22)(23)(24)(25)(26)(27)(28) raised the model that recombination occurred in the RBD region in the derivation of SARS-CoV-2, the lack of a singular dip in the landscape of pangolin-SARS-CoV-2 variation in the region would seem counterintuitive were SARS-CoV-2 a result of a localized recombination between a close relative of RaTG13 and a close relative of the putative pangolin coronaviruses under consideration. Thus alternative models for the observed sequence variation seem important to consider and indeed parsimonious, including that of selection acting on the RaTG13 sequences in bats or another intermediate host resulting in a rapid variation of the amino acids at the highly critical virus-receptor interface.…”
Section: Bat Virus Ratg13mentioning
confidence: 99%
“…A number of literature contributions now discuss the potential role for bats, pangolins, and other possible progenitor/intermediate species in derivation of SARS-CoV-2 from different approaches and perspectives, with a diversity of approaches and interpretations in understanding the origin of the virus. In particular, there has been extensive discussion and debate about the possible pangolin origin of SARS-CoV-2 (19,(21)(22)(23)(24)(25)(26)(27)(28)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). These studies provide useful insights into the evolution of SARS-CoV-2 but have limitations and uncertainty in drawing conclusions regarding the viral origin, as most studies were mainly performed through sequence-based comparison and simulation.…”
Section: Bat Virus Ratg13mentioning
confidence: 99%
“…The identity and network of covariant residues in this region are unique based on matching mutations to those in bat viruses including those most similar such as RATG13 suggesting that this genomic region in SARS-CoV-2 experienced different selective pressures and evolutionary history (Figure 2A and 2B). The 3'-boundary of this region is aligned to a recombinational hotspot (Tagliamonte et al, 2020) and this suggests that hybridization of different CoV isolates likely led to the emergence of SARS-CoV-2. Though this region of SARS-CoV-2 is most similar to RATG13, the divergence of covariance residues between bat and pangolin CoVs here provides strong evidence that parts of SARS-CoV-2 emerged from an independent distinct source ( Figure 2C).…”
Section: Resultsmentioning
confidence: 98%